An intact gut microbiota may be required for lactoferrin-driven immunomodulation in rats. (December 2017) - Wen, Yongping; He, Qiuwen; Ma, Da; Hou, Qiangchuan; Zhang, Heping; Kwok, Lai-Yu
Graphical abstract: Highlights: Lactoferrin ingestion shifted the overall fecal microbiota. Prolonged lactoferrin ingestion was required for the fecal microbiota modulation. The gut microbiota might be involved in lactoferrin-induced immunomodulation. Abstract: Lactoferrin can modulate both the host immunity and gut microbiota. However, whether the immune modulation requires the gut microbiota has not been directly shown. Thus, our study compared (1) lactoferrin-driven immunomodulation profiles and (2) changes in fecal phylogenic metagenome with and without antibiotics-induced dysbiosis in rats. Rats receiving only lactoferrin but not both lactoferrin and antibiotics had a Th-1 type cytokine serum profile. Significant differences were detected between the fecal microbiota of the lactoferrin and control groups at day 19 and/or day 33 but not initially, with a shift in the major contributors for community dissimilarity to Clostridium, Lactobacillus, and Oscillibacter valericigenes . The antibiotics-induced dysbiosis enriched the proinflammatory phyla, Proteobacteria and Deferribacteres, together with the anti-inflammatory species, Akkermansia muciniphila, while suppressed some butyrate-producers from the Firmicutes phylum. Our study shows that an intact microbiota is necessary for lactoferrin-driven immunomodulation.